Formic acid, a biomass-derived source of energy and hydrogen for biomass upgrading. Issue 9 (12th July 2019) - Valentini, Federica; Kozell, Vadym; Petrucci, Chiara; Marrocchi, Assunta; Gu, Yanlong; Gelman, Dmitri; Vaccaro, Luigi
Abstract : Formic acid is a main product from biomass-derived carbohydrates and is attracting ever more attention as a hydrogen source for a sustainable chemical production. Abstract : Formic acid is a main product from biomass-derived carbohydrates and is attracting ever more attention as a sustainable hydrogen source, owing to its high volumetric hydrogen density of 53 g of H2 per liter. In this review, we give an overview of the formic acid mediated transformations of biomass-based feedstocks into added-value products, including biofuels; attention will be primarily focused on the transformation of biomass-derived platform chemicals, with an emphasis on levulinic acid. Formic-acid mediated lignin depolymerization and biomass-oil upgrading will be also discussed.